Analysis of the Effect of Beauty Product Marketing Mix on Buying Interest with the Use of South Korean Celebrity Brand Ambassadors as a Moderation Variable - Siregar, Qurratu Ayuni; Wibowo, Rulianda Purnomo; Sembiring, Beby Karina Fawzeea (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
In the highly competitive beauty product industry, companies are required to implement innovative and relevant marketing strategies to maintain and increase consumer buying interest. Recent phenomena indicate that marketing mix elements (product, price, place, and promotion) are often underutilized or focused too narrowly on a single aspect. Meanwhile, the use of brand ambassadors, particularly South Korean celebrities, has become a dominant trend, believed to build emotional appeal and enhance positive consumer perceptions. This study aims to analyze the influence of the marketing mix and brand ambassadors on buying interest, as well as examine the moderating role of brand ambassadors in this relationship. This research adopts a quantitative associative approach, using questionnaires distributed to consumers exposed to brand ambassador promotional campaigns. Data analysis was conducted using multiple linear regression and moderated regression analysis. The results indicate that both the marketing mix and brand ambassadors have a positive and significant effect on consumer buying interest. However, the role of brand ambassadors as a moderating variable in strengthening the relationship between the marketing mix and buying interest was not consistently significant. These findings emphasize the importance of an integrated marketing strategy that not only leverages the popularity of brand ambassadors but also optimizes all elements of the marketing mix in a way that is appealing, educational, and aligned with contemporary consumer needs.